Atomic layer deposition: an enabling technology for the growth of functional nanoscale semiconductors - Biyikli, Necmi; Haider, Ali (Semiconductor science and technology, 2017)
In this paper, we present the progress in the growth of nanoscale semiconductors grown via atomic layer deposition (ALD). After the adoption by semiconductor chip industry, ALD became a widespread tool to grow functional films and conformal ultra-thin coatings for various applications. Based on self-limiting and ligand-exchange-based surface reactions, ALD enabled the low-temperature growth of nanoscale dielectric, metal, and semiconductor materials. Being able to deposit wafer-scale uniform semiconductor films at relatively low-temperatures, with sub-monolayer thickness control and ultimate conformality, makes ALD attractive for semiconductor device applications. Towards this end, precursors and low-temperature growth recipes are developed to deposit crystalline thin films for compound and elemental semiconductors. Conventional thermal ALD as well as plasma-assisted and radical-enhanced techniques have been exploited to achieve device-compatible film quality. Metal-oxides, III-nitrides, sulfides, and selenides are among the most popular semiconductor material families studied via ALD technology. Besides thin films, ALD can grow nanostructured semiconductors as well using either template-assisted growth methods or bottom-up controlled nucleation mechanisms. Among the demonstrated semiconductor nanostructures are nanoparticles, nano/quantum-dots, nanowires, nanotubes, nanofibers, nanopillars, hollow and core-shell versions of the afore-mentioned nanostructures, and 2D materials including transition metal dichalcogenides and graphene. ALD-grown nanoscale semiconductor materials find applications in a vast amount of applications including functional coatings, catalysis and photocatalysis, renewable energy conversion and storage, chemical sensing, opto-electronics, and flexible electronics. In this review, we give an overview of the current state-of-the-art in ALD-based nanoscale semiconductor research including the already demonstrated and future applications.